Numerical analysis of Cu(In, Ga)Se2 solar cells with high defect density layer at back side of absorber. Issue 6 (9th April 2015) - Ashida, Naoki; Murata, Masashi; Hironiwa, Daisuke; Chantana, Jakapan; Uegaki, Hikaru; Minemoto, Takashi; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; Shirakata, Sho; Wada, Takahiro; Niki, Shigeru; et al.
Abstract The 2‐µm‐thick Cu(In, Ga)Se2 (CIGS) absorber is divided into two areas, low defect density layer (front side) and high defect density layer (back side). In this paper, the optimized thickness of the low defect density layer and the high defect density layer is estimated for high cell performance. The optimization is performed by using device simulator. As a result, the high defect density layer (back side) has no influence on cell performance in the case of CIGS with high optical‐absorption coefficient owing to almost no photocarriers, which are generated in the high defect density layer. In addition, the necessary thickness for absorbing all light to obtain high conversion efficiency is considered. CIGS with graded band profile can be thinner than that with flat band profile for high cell performance owing to the aid of back surface field. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)